2019
DOI: 10.21203/rs.2.200/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of inferior vena cava collapsibility index in the prediction of hypotension associated with general anesthesia: an observational study

Abstract: Background: Intraoperative hypotension increases 30-day mortality and the risks of myocardial injury and acute renal failure. Patients with inadequate volume reserve before the induction of anesthesia are highly exposed. The identification of latent hypovolemia is therefore crucial. Ultrasonographic measurement of the inferior vena cava collapsibility index (IVCCI) is able to detect volume responsiveness in circulatory shock. No current evidence is available regarding whether preoperative measurement of the IV… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…As the aforementioned guidelines promote restrictive intra-and postoperative uid therapy, and in the same time alerts anaesthesiologist of the detrimental effects of the liberal use of vasopressors, it is vital to identify patients at risk before procedures. Point-of-care ultrasound was veri ed as a promising non-invasive method in several studies, where results offered pointing out patients with a potentially modi able [13,15,16,18]. Despite its obvious limitations (e.g., respiratory efforts, right ventricular dysfunction, pericardial disease, higher intraabdominal pressures) [35], the measurement of IVCCI was validated as a tool to guide uid load before subarachnoid blockade and it effectively helped prevent hypotension [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the aforementioned guidelines promote restrictive intra-and postoperative uid therapy, and in the same time alerts anaesthesiologist of the detrimental effects of the liberal use of vasopressors, it is vital to identify patients at risk before procedures. Point-of-care ultrasound was veri ed as a promising non-invasive method in several studies, where results offered pointing out patients with a potentially modi able [13,15,16,18]. Despite its obvious limitations (e.g., respiratory efforts, right ventricular dysfunction, pericardial disease, higher intraabdominal pressures) [35], the measurement of IVCCI was validated as a tool to guide uid load before subarachnoid blockade and it effectively helped prevent hypotension [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Most protocols estimate patients' volume status, and many of them rely on the respiratory variations of the inferior vena cava for this purpose. Although the well-documented methods of preload assessment are less accurate estimates of the uid status or uid responsiveness when used on spontaneously breathing patients [9,10] than in the case of mechanical ventilation [11,12], several studies including our previous experiences identi ed their potential role prior to general anaesthesia [13][14][15][16]. Even though a recent study showed the superiority of variations of left ventricular out ow velocity-time integral (LVOT-VTI) in the prediction of intraoperative hypotension [13], the feasibility of the evaluation of IVC collapsibility index (further IVCCI) still makes it a potential choice to guide perioperative uid therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Patients exhibiting autonomic dysfunction and poor blood volume are more likely to develop PIH [6,7]. Blood volume status can be assessed through ultrasonographic measurements of the diameter of the inferior vena cava or subclavian vein and associated collapsibility indices, providing an accurate and rapid means of gauging PIH risk [7][8][9]. In contrast, the relationship between autonomic dysfunction and PIH remains incompletely understood, with heart rate variability (HRV) being the only generally accepted approach to assessing the autonomic nerve function of a given patient despite its high technical requirements and relatively poor ability to accurately predict PIH incidence [6,10].…”
Section: Open Accessmentioning
confidence: 99%
“…Seven of these studies could best be described as positive [32][33][34][35][36][37][38] and 5 negative. [39][40][41][42][43] again leaving us in a position of uncertainty. Contrary to popular belief, therefore, it does not seem at all certain that IVC analysis performs better in this patient population.…”
Section: Individual Studies In Mechanically Ventilated Patientsmentioning
confidence: 99%